46. CASE REPORT: TREATMENT OF TRIGEMINAL NEURALGIA WITH BOTULINUM TOXIN A INJECTIONS (Vietnam Journal of Community Medicine, 2024)
Objective: to evaluate the efficacy of Botulinum toxin type A (BTX-A) in treating trigeminal neuralgiaSubject and method: case report. A female patient with trigeminal neuralgia was treated with BTX-A injections into the sensitive distribution of the trigeminal nerve. Pain levels were assessed using a standard pain scale before and after treatment.Results: The patient experienced significant pain reduction, with pain scores decreasing from 10/10 to 2/10 after injection and the effect lasted for a long period of time with no serious side effects reported.Conclusion: BTX-A injections provided substantial and prolonged pain relief in trigeminal neuralgia patients. This suggests that BTX-A is a viable, less invasive alternative for managing trigeminal pain.
Keywords: trigeminal neuralgia; Botulinum toxin type A; pain management; neuralgia treatment; case report